Association of neutrophil-to-lymphocyte ratio and monocyte-tolymphocyte ratio with all-cause mortality in patients with ischemia and non-obstructive coronary arteries - Mihai Emilian Dumitru; Delcea Caterina; Buzea Adrian Cătălin; Dan Gheorghe-Andrei (Romanian Journal of Laboratory Medicine)
Ischemia with non-obstructive coronary arteries (INOCA) is a frequent coronary syndrome with important impact on morbimortality. Systemic inflammation, a key pathophysiological mechanism in its development, is reflected in diverse bio-markers, such as the neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR) and platelet-to-lymphocyte ratio (PLR). In this retrospective observational study, we aimed to assess the value of NLR, MLR and PLR as predictors of all-cause long-term mortality in INOCA patients.